O dever ético e constitucional na atribuição de um valor intrínseco à natureza e o papel pedagógico da jurisdição na formação de uma cultura ambiental autêntica - Leonardelli, Pavlova Perizzollo (My University, 2014)
The authentic environmental culture, built on the solid foundations of environmental ethics and ecological literacy provides the spontaneous fulfillment of ethical and constitutional obligation of preserving the environment. The jurisdiction, through paradigm decisions in favor of the environment, indicates the position of the State and thus contributes to the construction of this new authentic environmental culture. Initially, it is considered that the relationship between man and the environment has undergone major transformation in the sixteenth and seventeenth centuries. The scientific revolution had strong influence on Western countries, which have adopted anthropocentrism replacing theocentrism that until then prevailed. Since then, humans began a trajectory of domination of nature, extracting her everything he believed to be good for humanity, without measuring the consequences and treating the nature as an object. Symptoms indicating the emergence of an environmental crisis began to appear, demonstrating the need for changes to reverse the situation that was installed there. In terms of environmental legislation, Brazil innovated significantly; however, the legal regulations are ineffective. Because of that, necessary reform of thought and the consequent disruption of the mechanistic paradigm still dominant. The way how the humanity interprets the nature needs to be reviewed and overhauled, structured by an ethic and authentic environmental culture, focused in protection, preservation and responsibility to the universe in the present and also in the future. Thus also fulfills the principle of human dignity, which constitutes one of the foundations of the democratic rule of law, expressed on the Constitution of 1988. The state has a constitutional obligation to preserve and maintain the environment. Thus, through the environmental education and the jurisdictional praxis, the environmental pedagogy completes and spreads throughout society. The resulting decisions of the courts and the constitutional court demonstrate in practice how much contribute to build an environmental culture that involves both the ethics and the fulfillment of the legal obligation to preserve and maintain ecologically balanced environment, all spontaneously and above all, authentic.
A cultura ambiental autêntica, construída sobre as sólidas bases da ética ambiental e da alfabetização ecológica proporciona o cumprimento espontâneo do dever ético e constitucional da preservação do meio ambiente. A jurisdição, através de decisões paradigma em prol do ambiente, indica o posicionamento do Estado e dessa forma contribui para a construção dessa nova cultura ambiental autêntica. Inicialmente, considera-se que a relação do homem com o meio ambiente sofreu grande transformação nos séculos XVI e XVII. A revolução científica teve forte influência sobre os países do ocidente, que adotaram o antropocentrismo em substituição ao teocentrismo que até aquele momento vigorava. A partir de então, o ser humano iniciou uma trajetória de domínio da natureza, extraindo dela tudo o que acreditava ser bom para a humanidade, sem medir consequências e tratando a natureza pura e simplesmente como objeto. Os sintomas que indicavam o surgimento de uma crise ambiental começaram a aparecer, demonstrando a necessidade de mudanças para reverter a situação que ali se instalava. Em termos de legislação ambiental, o Brasil inovou de forma significativa, contudo, as normas ainda são pouco eficazes. Em virtude disso, necessária a reforma do pensamento e o consequente rompimento do paradigma mecanicista ainda vigente. A forma como a humanidade interpreta a natureza precisa ser revista e remodelada, estruturada por uma cultura ambiental ética e autêntica, com vistas a proteção, preservação e responsabilidade com o universo do presente e também com o futuro. Desta forma também se cumpre o princípio da dignidade da pessoa humana, que se constitui como um dos fundamentos do Estado Democrático de Direito, expresso na Constituição de 1988. O Estado tem o dever constitucional de preservar e manter o meio ambiente. Assim, através da educação ambiental e da práxis jurisdicional, a pedagogia ambiental se perfaz e se dissemina por toda a sociedade. As decisões advindas dos tribunais e da corte constitucional demonstram na prática o quanto contribuem para a construção de uma cultura ambiental que envolva simultaneamente a ética e o cumprimento do dever legal de preservar e manter o ambiente ecologicamente equilibrado, tudo de forma espontânea e, sobretudo, autêntica.
Keywords: Direito ambiental; Meio ambiente; Ética; Jurisdição; Environmental law; Ethics